2020
DOI: 10.3390/genes11060619
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis and Genetic Counseling of Cystic Fibrosis and Related Disorders: New Challenges

Abstract: Identification of the cystic fibrosis transmembrane conductance regulator (CFTR) gene and its numerous variants opened the way to fantastic breakthroughs in diagnosis, research and treatment of cystic fibrosis (CF). The current and future challenges of molecular diagnosis of CF and CFTR-related disorders and of genetic counseling are here reviewed. Technological advances have enabled to make a diagnosis of CF with a sensitivity of 99% by using next generation sequencing in a single step. The detection of heret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 77 publications
1
19
0
1
Order By: Relevance
“…Different combinations of CFTR variants, many of which result in residual CFTR function, have been associated with CFTR-related disorders (CFTR-RDs), the mildest of which is congenital absence of the vas deferens (CAVD [MIM: 277180]) in males with no evidence of lung disease. 4,5 For several CFTR variants, functional assays have demonstrated the resulting residual CFTR activity, [6][7][8] but for many missense variants, the functional effect is unknown. Finally, different combinations of ABCA4 variants (GenBank: NM_000350.2) can result in multiple retinal phenotypes, i.e., early-onset cone-rod dystrophy-sometimes diagnosed as retinitis pigmentosa (retinitis pigmentosa 19 [MIM: 601718])-panretinal cone-rod dystrophy (cone-rod dystrophy 3 [MIM: 604116]), due to the early degeneration of both cone and rod cells; classic Stargardt disease (STGD1); or late-onset macular degeneration (STGD1 [MIM: 248200]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different combinations of CFTR variants, many of which result in residual CFTR function, have been associated with CFTR-related disorders (CFTR-RDs), the mildest of which is congenital absence of the vas deferens (CAVD [MIM: 277180]) in males with no evidence of lung disease. 4,5 For several CFTR variants, functional assays have demonstrated the resulting residual CFTR activity, [6][7][8] but for many missense variants, the functional effect is unknown. Finally, different combinations of ABCA4 variants (GenBank: NM_000350.2) can result in multiple retinal phenotypes, i.e., early-onset cone-rod dystrophy-sometimes diagnosed as retinitis pigmentosa (retinitis pigmentosa 19 [MIM: 601718])-panretinal cone-rod dystrophy (cone-rod dystrophy 3 [MIM: 604116]), due to the early degeneration of both cone and rod cells; classic Stargardt disease (STGD1); or late-onset macular degeneration (STGD1 [MIM: 248200]).…”
Section: Introductionmentioning
confidence: 99%
“…Existing guidelines for the interpretation of pathogenicity of variants are not tailored to assess variant severity. The commonly used 5-tier American College of Medical Genetics and Genomics and the Association for Molecular Pathology (ACMG-AMP) system addresses the likelihood of a variant's pathogenicity on a scale from benign (1) to pathogenic (5), which in no way relates to its severity. 37 For instance, the frequent mild ABCA4 variant c.5882G>A (p.Gly1961Glu) is considered ''likely pathogenic'' according to the ACMG-AMP guidelines, whereas variants classified as variants of uncertain significance by ACMG-AMP may well cause a severe phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…This nding is consistent with previous study. For example, the carrier frequency of I556V in Asia population is as high as 4.7% [17]. This uncovers the different allele frequency and incomplete penetrance among different populations.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have reported different founder variants of CFTR in various races. F508del was reported to account for 30-88% CFTR pathogenic variants in non-Chinese populations [17]. Besides, Pompei et al found that most variants were associated with the M470V allele in several European populations which can help to trace the origin of the V allele [19].…”
Section: Discussionmentioning
confidence: 99%
“…With the implementation of carrier screening tests [ 19 ], a gynaecologist can also evaluate the risk of a couple (or even gamete donors) of carrying genetic variants responsible for autosomal recessive or an X-linked genetic disease. Thus, they might be able to reduce the risks of having an affected child with diseases, such as cystic fibrosis [ 46 ] or X-fragile by the use of preimplantation genetic diagnosis (PGD) [ 47 ]. Also, prenatal genetic testing (either non-invasive as a screening method or invasive as a diagnostic tool) might allow early detection of genetic abnormalities.…”
Section: Genetic Services (Including Genetic Counselling) For Rare Diseases In Spainmentioning
confidence: 99%